National Security Strategies Amidst Increasing Global Cyber Threats: A Multilateral Approach - Loso Judijanto (Pt. Anagata Sembagi Education, 2024)
In today's digital age, the development of information technology has a significant impact on various sectors, including the economy, politics and security. While technology provides opportunities for efficiency and innovation, it also introduces increasingly complex cyber threats. Cyberattacks now target not only individuals, but also large institutions, multinational corporations and governments, resulting in economic losses and threatening the socio-political stability of a country. Indonesia, like many other countries, faces growing cyber threats, including e-HAC data leaks and ransomware attacks. These threats require a multilateral approach due to their cross-border nature and the involvement of highly capable actors, whether individuals, criminal groups or specific states. This research aims to explore national security strategies in dealing with global cyber threats through a multilateral approach. The main focus is to identify how international cooperation can improve the effectiveness of a country's cybersecurity and analyze the challenges in implementing this strategy. Using a qualitative approach and descriptive-analytical design, this research collected secondary data from official documents, reports of international organizations, as well as relevant journal articles. The results of this research are expected to provide useful recommendations for policymakers in formulating national security strategies that are more resilient and responsive to evolving cyber threats